Analysis of Service Quality on Outpatient Satisfaction at the Clinic Asy-syifa Darul Hidayah Hulu Sungai Tengah - Fanlia Adiprimadana Sanjaya; Fanlia Prima Jaya (PT. Hanken Sukses Jaya, 2022)
The importance of access to health makes people need fast and appropriate services so several clinics are present that help the community in getting their health checked, especially in the Hulu Sungai Tengah district. Improving the quality of health services can be improved, so that the goal of the clinic can be to make patients or consumers satisfied with the services offered or provided. At the Asy-Syifa clinic Darul Hidayah Hulu Sungai Tengah, it is necessary to improve the quality of health services because there are still several complaints from patients and their families due to the long waiting time and lack of communication from officers, starting from the registration section, the examination section, to the drug service section so that they can improve to provide a satisfactory service impact both from the officers, the comfort of the place and the completeness of the supporting equipment. The Effect of Service Quality on Patient Satisfaction at the Asy-Syifa Darul Hidayah Clinic, Hulu Sungai Tengah, has a significant effect on patient satisfaction, therefore by improving the quality of clinical services, will have an impact on the satisfaction felt by patients.